Pengaruh Intensitas Modal, Intensitas Persediaan, Profitabilitas, dan Koneksi Politik terhadap Agresivitas Pajak dengan Komisaris Independen sebagai Variabel Moderasi - Rivan Andi Ghifary; Hexana Sri Lastati (Syntax Corporation Indonesia, 2024)
This study aims to analyze the effect of capital intensity, inventory intensity, profitability, and political connection on tax aggressiveness with independent commissioners as variable moderation. The population of this research is listed on Indonesia Stock Exchange in 2017-2021 and the samples tested in this study were 78 data taken based on the purposive sampling. The data used in this study are secondary data from annual reports and financial reports. This study used multiple linear regression analysis and moderated regression analysis. The results of this research showed that the variable.